Juvenile Barn Owl Tyto alba dispersal: a radio-tracking study of roost site selection in relation to landscape features. Issue 2 (3rd April 2021) - Ruiz, Mateo D. M.; Ramsden, David; Roper, Simon; Cresswell, Brian; Skuse, Jack
ABSTRACT: Capsule: Radio-tracking of 19 juvenile Barn Owls Tyto alba alba in England revealed different spatial patterns for males and females, that tree branches were frequent roost sites, and that altitudinal distribution changed after owls acquired home ranges. Aims: To gain new understanding of the natal dispersal of Barn Owls by identifying roost sites and analysing their spatial pattern, site type, altitude, and location in relation to linear features. Methods: Diurnal roost sites of 19 juvenile Barn Owls were located by radio-tracking in southwest England. We evaluated the possibility of sex-bias in natal and between-roost dispersal distances and tested for change in the site types used as natal sites and daytime roosts. We tested for differences in the altitude of roosts used during the dispersal phase and those used once the birds acquired a home range, and we analysed the location of roost sites in relation to major roads, railways, and rivers. Results: Barn Owls commenced dispersal when they were between 63 and 122 days after hatching (median = 94). Roost sites used by females were more widely scattered than those used by males. Owls roosted most frequently in trees, despite most natal sites being in buildings. The altitude of roost sites during dispersal in elevated landscapes was higher than those on their acquired home range. We could find no evidence that owls followed linear features during dispersal, nor that hills were barriers to dispersal. Conclusion: Post-fledging roosting behaviour of female and male Barn Owls differed spatially and was congruent with a wider pattern of sex-bias in avian natal dispersal. Frequent roosting on tree branches had implications for exposure to adverse weather. Some juveniles roosted at altitudes that were higher than subsequent roosts on their acquired home range. We found no evidence to support the proposal that linear landscape features constituted dispersal corridors.